Performances of upgraded Dwarf-Fayoumi chicken genotype in different feeding systems under smallholder farm management (Bangladesh Journal of Animal Science, 2024)
The experiment was conducted to evaluate the performance of upgraded Dwarf-Fayoumi genotype (IDC♂ × Fay♀) with three different feeding regimes from onset of lay to 72 weeks of age. A total of 90 IDC♂ × Fay♀ birds of third generation (F3) at 16 weeks of age were distributed to 15 selected farmers nearby three villages of Bangladesh Agricultural University, Mymensingh. The villages were Kewatkhali, Boyra and Sutiakhali that selected for intensive, semi-scavenging and scavenging feeding systems, respectively. Each farmer was also given 5 pullets and 1 cockerel. The birds of full feeding and semi-scavenging system were given 76 g and 38 g mash feed per day, respectively. Pullets of semi-scavenging condition were allowed to scavenge in the farmer homesteads. The birds under scavenging condition reared without supplementation and were allowed to scavenge all day long. Result showed a significant difference (p